OpenCV : computer vision projects with Python : get savvy with OpenCV and actualize cool computer vision applications : a course in three modules.: computer vision projects with Python : get savvy with OpenCV and actualize cool computer vision applications : a course in three modules. (2016) - Howse, Joseph, 1984-; Joshi, Prateek; Beyeler, Michael
No abstract available